Genomic profile of eGFP-expressing canine distemper virus that undergoes serial plaque-to-plaque transfers - Lin, Jiahui; Jiang, Yujia; Zhang, Hui; Zhang, Feng; Zhang, Youming; Ni, Bo; Liu, Fuxiao (Frontiers in Cellular and Infection Microbiology, 2022)
Canine distemper virus (CDV) is classified into the genus Morbillivirus in the family Paramyxoviridae. This virus has a single-stranded genomic RNA with negative polarity. The wild-type CDV genome is generally composed of 15 690 nucleotides. We previously rescued an enhanced green fluorescence protein (eGFP)-tagged recombinant CDV (rCDV-eGFP) using reverse genetics. In this study, the rCDV-eGFP at passage-7 was subjected to 38 serial plaque-to-plaque transfers (or bottleneck passages) and two extra common passages in cells. In theory, the effect of Muller's ratchet may fix deleterious mutations in a single viral population after consecutive plaque-to-plaque transfers. In order to uncover a mutated landscape of the rCDV-eGFP under the circumstances of bottleneck passages, the passage-47 progeny was collected for the in-depth analysis via next-generation sequencing. The result revealed a total of nine single-nucleotide mutations (SNMs) in the viral antigenome. Out of them, SNMs at nt 1832, 5022, 5536, 5580, 5746, 6913 and 8803 were identified as total single-nucleotide substitution, i.e., 100% of mutation frequency. The result suggested no notable formation of viral quasispecies in the rCDV-eGFP population after consecutive plaque-to-plaque transfers.